Legal Protection Of Indonesian Migrant Workers In Malaysia From The International Labor Organization (ILO) Perspective - Habib, Yahya Abdul; Roestamy, Martin; Suhartini, Endeh (IJBLE Scientific Publications Community Inc., 2024)
Work is the need for everyone to meet the needs of life for themselves and their families. Indonesian migrant workers have high hopes for improving their lives to achieve the welfare of themselves and their families, one of which is by working in Malaysia. This study uses an empirical juridical method with direct interview and observation methods in Malaysia and related parties to obtain accurate data. Some conditions and problems occur for Indonesian migrant workers working in Malaysia. In working in Malaysia as an Indonesian Migrant Worker, you must go through stages according to the provisions of the Law, and if violated, there are strict sanctions. The UN agency that handles Manpower issues, or the ILO, must provide strict supervision and guidance for Legal Protection and Legal Certainty for everyone who works abroad. Good coordination between the Central and Regional Governments, especially in Indonesia, is essential so that cases against Indonesian Migrant Workers can be appropriately handled.